PERTUMBUHAN KREDIT PERBANKAN DI INDONESIA: INTERMEDIASI DAN PENGARUH VARIABEL MAKRO EKONOMI - Haryati, Sri (Jurnal Keuangan dan Perbankan, 2009)
The purpose of the research was to provide empirical evidence on the variables thataffected loan growth. The variables used to assess fund resources and allocation were depositgrowth, borrowing growth, equity growth, excess liquidity (secondary reserve) growth; andthe variables used to assess macro economics were BI rate, inflation and exchange rate. Theresearch population was all banks which operated in Indonesia and divided into two groups:national bank and foreign bank; and the secondary data was the publication of bank financialstatements of four time perception which were during December 2004-December 2008. Multipleregression was used for instrument analysis. The result of the research showed that two variablesfunds resources represented significant determination of loan growth on the national bank,and three variables fund resources represented significant determination of loan growth onforeign bank. All variables macro-economics represented significant determination of loangrowth on national bank, but not significant on foreign bank. The result of the Chow testshowed that the regression model for two group banks that operated in Indonesia was different.